Pesan Moral Dalam Iklan Bibit Versi “Suara Hati Generasi Sandwich” : Analisis Semiotika Charles Sanders Pierce - Irsyad Renaldi; Daniel Handoko (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Advertising is a form of non-personal presentation and promotion of ideas, goods, or services by certain parties that are required to pay to spread the desired message, it can also be to build preferences to educate people or brands, forms of advertising can be in the form of electronic media and print media, magazines etc.. The advertising communication contains information about the existence of the product through images, words, writing and sound processed with an attractive display to encourage the audience to make purchases of the advertised product and so that the attractiveness of this advertisement is more able to influence the audience This study aims to identify signs and analyze the moral messages contained in the Bibit advertisement version